Dr. Salah Esam — Deep Plane Facelift — Cairo - Esam, Salah (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Salah Esam, practicing in Cairo, Egypt. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003106; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; egypt; cairo